1992
DOI: 10.1017/s0950268800049931
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and characteristics of verocytotoxigenicEscherichia coliisolated from Ontario dairy cattle

Abstract: SU MMARYFaecal swabs obtained from a random sample of 1131 cows and 659 calves on 100 southern Ontario dairy farms were examined for verocytotoxigenic Escherichia coli (VTEC) using a Vero cell assay. Five isolates from each positive culture were tested similarly. Positive colonies were examined with DNA probes for Shiga-like toxin I (SLT-I) and SLT-II sequences. Probe-negative colonies were tested for nieutralization of verocytotoxicity using anti-SLT-I and anti-SLT-Ilv antisera.Colonies showing Ino neutraliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
56
3
2

Year Published

1993
1993
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 20 publications
14
56
3
2
Order By: Relevance
“…The high carriage rate of VTEC in cattle also indicated that they were reservoirs for transmission of the organism. In other geographic areas, VTEC carriage rates in healthy cattle have been reported to be 34 % in France [18], 24n3 % in Japan [7], 53 % in Sri Lanka [19] and 9n5 % in Canada [8]. Our highest carriage rate occurred during the coolest months, which contrasts with the finding in France where the highest VTEC prevalence was in summer [18].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The high carriage rate of VTEC in cattle also indicated that they were reservoirs for transmission of the organism. In other geographic areas, VTEC carriage rates in healthy cattle have been reported to be 34 % in France [18], 24n3 % in Japan [7], 53 % in Sri Lanka [19] and 9n5 % in Canada [8]. Our highest carriage rate occurred during the coolest months, which contrasts with the finding in France where the highest VTEC prevalence was in summer [18].…”
Section: Discussioncontrasting
confidence: 63%
“…The epidemiology of VTEC in man and animals has been studied in Western countries and Japan [6][7][8] but data from South East Asia and China are sparse. In this study, faecal and carcass samples were collected from cattle and pigs in an abattoir in Hong Kong, in an attempt to study the frequency of VTEC carriage in healthy livestock in the province.…”
Section: Introductionmentioning
confidence: 99%
“…This serotype is also the most frequent cause of outbreaks in daycare centres and other institutions [6][7][8][9]. Other VTEC strains of diverse serotypes including those causing diarrhoea and HUS in humans are frequently isolated from animal faeces, meat and dairy products [10][11][12][13][14][15][16][17]. Cattle have been implicated as the principal reservoir for VTEC [16,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Detection and isolation of STEC was undertaken as described previously, with some modifications. 22 A 100-l quantity of each fecal culture frozen in glycerol was inoculated into 5 ml of modified tryptic soy broth containing 20 g/ml novobiocin (mTSBϩn) and incubated overnight at 37C. Filtrates of the resulting culture were screened for the presence of STx by the Vero cell cytotoxicity assay (VCA) as described previously, except that filtrates were tested at 3 5-fold dilutions and the plates were read microscopically after 48 hours.…”
mentioning
confidence: 99%